Popular religion in Southeast Asia - Winzeler, Robert L. (Rowman & Littlefield, 2016)
The development of religion in Southeast Asia -- Three versions of popular Hinduism -- Buddhism and popular religion -- Popular Islam in Malaysia and Indonesia -- Conversion and popular Christianity -- The magic of the market -- Religious movements as popular religion -- Popular religion in Southeast Asia